Does Dysmenorrhea Affect Clinical Features and Long-Term Surgical Outcomes of Patients With Ovarian Endometriosis? A 12-Year Retrospective Observational Cohort Study - Wu, Yushi; Li, Xiaoyan; Dai, Yi; Shi, Jinghua; Gu, Zhiyue; Zhang, Jing; Zhang, Chenyu; Yan, Hailan; Leng, Jinhua (Frontiers in Medicine, 2022)
Background To examine and compare the differences in clinical characteristics and long-term postoperative outcomes of ovarian endometriomas (OMA) patients with and without dysmenorrhea, including data from at least 8 years of postoperative follow-up examinations. Methods Retrospective analysis of 334 OMA patients, including their demographic and clinical data. Long-term follow-up record was also collected. All laparoscopic cystectomy procedures were performed by the same surgeon at Peking Union Medical College Hospital between January 2009 and April 2013. Patients were divided into the dysmenorrhea and non-dysmenorrhea groups to perform the analysis of their preoperative characteristics, relevant surgical findings, and postoperative outcomes at the follow-up. Results Out of 334 OMA patients, 257 (76.9%) patients were allocated to the dysmenorrhea group, while the rest 77 (23.1%) patients were included in the non-dysmenorrhea group. Compared with the dysmenorrhea group, the non-dysmenorrhea group exhibited a reduced proportion of chronic pelvic pain (CPP) (P = 0.003), dyspareunia (P < 0.001), tenesmus (P < 0.001), concurrency of deep infiltrating endometriosis (DIE) (P < 0.001), and adenomyosis (P = 0.032). Preoperative infertility was significantly higher in the dysmenorrhea group (P = 0.001). The mean operating time in the dysmenorrhea vs. the non-dysmenorrhea group was 68.0 vs. 56.0 min (P < 0.001). According to the revised American Fertility Society (rAFS) scoring system, the mean scores of the two groups were 52.1 vs. 44.6 (P = 0.033). During follow-up, the dysmenorrhea group showed a higher rate of disease relapse (P < 0.001). A minimum postoperative follow-up period of 8 years was required to evaluate the pregnancy outcomes. Successful pregnancies were identified in 97/257 (37.7%) cases in the dysmenorrhea group and 36/77(46.8%) cases in the non-dysmenorrhea group (P = 0.157), respectively. Though the dysmenorrhea group had a higher rate of postoperative infertility, differences were not significant between the two groups. Conclusions Compared with the dysmenorrhea group, OMA patients without dysmenorrhea exhibited lower proportions of CPP, dyspareunia, tenesmus, lower concurrency of DIE and adenomyosis, shorter mean operating time, lower mean rAFS scores, and lower infertility rates. During the long-term follow-up, a lower recurrence rate was observed in the non-dysmenorrhea group. Regarding fertility outcomes, non-dysmenorrhea patients had a higher likelihood of successful pregnancy after surgery. Postoperative management needs to be evaluated separately according to dysmenorrhea pathology.